2020
DOI: 10.1093/bib/bbaa207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative host–pathogen protein–protein interaction analysis of recent coronavirus outbreaks and important host targets identification

Abstract: Last two decades have witnessed several global infectious outbreaks. Among these, coronavirus is identified as a prime culprit ranging from its involvement in severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS) to COVID-19. These infections involved in huge healthcare and economic cost incurred globally. Every time, coronavirus improved its infection ability and surprised the medical practitioners and researchers. Currently, COVID-19 is also causing numerous infections and stalled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Previous research evidence has shown that TMPRSS2 plays an important role in monitoring the infection process of severe acute respiratory syndrome (Khoury et al, 2020;Suarez-Farinas et al) virus and Middle East respiratory syndrome (Lavin et al, 2017) coronavirus (Khan and Khan, 2021). Similarly, in a research report on SARS-CoV-2, TMPRSS2…”
Section: Discussionmentioning
confidence: 90%
“…Previous research evidence has shown that TMPRSS2 plays an important role in monitoring the infection process of severe acute respiratory syndrome (Khoury et al, 2020;Suarez-Farinas et al) virus and Middle East respiratory syndrome (Lavin et al, 2017) coronavirus (Khan and Khan, 2021). Similarly, in a research report on SARS-CoV-2, TMPRSS2…”
Section: Discussionmentioning
confidence: 90%
“…However, the analysis of virus-host interactomes is a field that stands on stony ground. Researchers are gradually beginning to recognize the importance of HP-PPIs and are starting to support this field, especially with the ongoing 2019 coronavirus pandemic (COVID -19) ( 52 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant efforts of global scientific community made several breakthroughs in understanding molecular basis of SARS-CoV2 pathogenesis. A large number of studies have reported SARS-CoV2 interactions with several host targets and their subsequent contribution in pathogenesis [28]. These interactions have been compiled in several interaction databases.…”
Section: Discussionmentioning
confidence: 99%